Synergistic-Influence of Sulphur and Boron on Enhancing the Productivity of Sesame (Sesamum indicum L.) Grown in an Entisol of Kerala - Sumam George, Jeena Mathew and (Journal of the Indian Society of Soil Science, 2013)
To evaluate the effect of sulphur (S) and boron (B) on the productivity of sesame (Sesamum indicum L.) in an Entisol of Kerala, a field experiment was laid out in a factorial RBD with 4 levels each of sulphur(0, 7.5, 15.0 and 30 kg S ha-1) and boron (0, 2.5, 5.0 and 7.5 kg B ha-1). Results showed that S and B acted synergistically in enhancing the biometric characters, root characters, yield and yield attributes of sesame, and nutrient uptake by grain and straw. The available nutrient status was also significantly improved by the application of these nutrients.